Character Building of Students Through Islamic Boarding School Education at Darul Hidayah Al Anshori Islamic Boarding School, West Tulang Bawang, Lampung - Nafi Satu Syarifah; Ehwanudin; Rina Mida Hayati (Institut Agama Islam Ma`arif NU (IAIMNU) Metro Lampung, 2026)
This study aims to analyze the character development patterns of female students at the Darul Hidayah Al-Anshori Islamic Boarding School in West Tulang Bawang, Lampung, and to identify the supporting and inhibiting factors. Using Thomas Lickona's theory, which encompasses three dimensions of character (moral knowing, moral feeling, and moral action), this qualitative study employed a case study approach. Data were collected through participant observation, in-depth interviews, and documentation of the female students and their female mentors. The results indicate that character development has succeeded in developing the moral knowing aspect through the study of Islamic scriptures and the moral action aspect through the habituation of worship and dormitory discipline. However, the moral feeling aspect still requires strengthening so that the female students perform good deeds based on conscience, not merely compliance with sanctions. The main supporting factors are the religious environment and the role models of educators, while obstacles arise from the heterogeneity of the students' backgrounds and the influence of the external environment.